Structural, optical and thermal properties of Zr–Fe co‐doped congruent LiNbO3 single crystals. (15th May 2013) - Riscob, B.; Bhatt, R.; Vijayan, N.; Bhaumik, Indranil; Ganesamoorthy, S.; Wahab, M. A.; ,; Bhagavannarayana, G.
<x xml:space="preserve">Abstract</x> Zr–Fe‐doped congruent lithium niobate single crystals were grown by the Czochralski technique. The crystal structure and lattice parameter of the grown crystals were assessed by powder X‐ray diffraction and the strain developed as a result of doping has been calculated (−1.19 × 10−3) by using the Williamson–Hall relation. The incorporated dopant concentration along with the dopant distribution in the specimen crystal was estimated by X‐ray florescence spectrometry. A multi‐crystal X‐ray diffraction analysis was carried out to identify the crystalline perfection of the sample and revealed that the investigated crystal does not contain any structural grain boundaries but does contain point defects and micrometre size mosaic blocks. Birefringence measurements were carried out using a prism coupler spectrometer and found that the optical birefringence is 0.0822 for 532 nm and 0.705 for 1064 nm. A thermal conductivity (κ) study reveals that the doped sample has a lower κ value than the undoped equivalent.